Pediatric rhabdomyolysis: a systematic review and meta-analysis of etiologies, management, and outcomes - Hany A. Zaki (17337673) (2025)
Background Rhabdomyolysis is a potentially fatal disorder that occurs due to various causes. Therefore, the aim of this meta-analysis was to identify the underlying causes, evaluate the treatment options, and determine the mortality and kidney outcomes of children with rhabdomyolysis. Methods We comprehensively searched PubMed, Cochrane Library, Web of Science, EMBASE, and Google Scholar databases for records written in English and published until April 2025. According to PICO criteria, we included studies that enrolled pediatric patients with rhabdomyolysis and reported etiologies, treatments, mortality, and/or kidney outcomes. Subsequently, quality appraisal was conducted with Newcastle Ottawa Scale and statistical analyses were performed using comprehensive meta-analysis (CMA) software. Results Fifteen studies enrolling 10,514 pediatric patients with rhabdomyolysis were reviewed and analyzed. The one-arm meta-analysis revealed that infections were the most predominant etiology of rhabdomyolysis (40.6%; 95% CI: 33.5 to 48.2), followed by trauma (19%; 95% CI: 15.5 to 23.0) and exercise (14.7%; 95% CI: 6.5 to 30.2). Other etiologies accounted for less than 10% of rhabdomyolysis cases i.e., burns (2.9%; 95% CI: 1.2 to 7.2), connective tissue disorder (2.7%; 95% CI: 0.7 to 9.6), drugs (5.8%; 95% CI: 3.1 to 10.6), metabolic abnormalities (4.4%; 95% CI: 3.0 to 6.6), multiorgan failure (4.1%; 95% CI: 1.0 to 15.5), muscular dystrophy (2.6%; 95% CI: 0.6 to 11.4), seizure (7.2%; 95% CI: 3.9 to 12.9), and sepsis (9.9%; 95% CI: 1.1 to 52.8). The pooled results also showed that the incidences of acute kidney injury (AKI) and chronic kidney disease (CKD) were 21.3% (95% CI: 14.5 to 30.3; I 2 = 96%) and 1.1% (95% CI: 0.7 to 2; I2 = 0%), respectively. The pooled mortality rate of children with rhabdomyolysis was 4.5% (95% CI: 1.7 to 11.8; I2 = 94.7%). Conclusions Infections are the leading causes of rhabdomyolysis in children. Moreover, AKI is a common complication of rhabdomyolysis in children. However, the prognosis of children with rhabdomyolysis is good and few patients progress to CKD. Systematic review protocol registration PROSPERO: CRD420251035968. Other Information Published in: BMC Pediatrics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12887-025-06081-x